(untitled) (Mediscope, 2023)
Background: Chronic kidney disease (CKD) is a worldwide public health problem. It is usually associated with hypertension (HTN) and diabetes mellitus (DM) and the prevalence of these complications increases progressively with worsening CKD. Objective: To find out the association of HTN and DM with different stages of CKD. Methods: This cross-sectional study was conducted at the Department of Physiology, Mymensingh Medical College, Bangladesh, for one year from January to December 2016. A total number of 73 diagnosed CKD patients and 73 non-CKD individuals were enrolled in the study. Blood pressure was measured by using a sphygmomanometer and stethoscope. Serum glucose concentrations were measured by using an auto-analyzer. Results: Hypertension and diabetes were more prevalent in CKD than in non-CKD individuals, which were statistically significant. Among 73 CKD patients, 42.5% were diagnosed as hypertensive, and 34.3% were diagnosed as diabetic. Conclusion: This study revealed that the prevalence of HTN and DM is common in all stages of CKD patients in Mymensingh, Bangladesh. It emphasizes the need for regular checking of blood pressure, blood glucose, serum creatinine and estimated glomerular filtration rate (eGFR) level in CKD patients and early referral to nephrologists. Mediscope 2023;10(2): 63-67